2018 IEEE Southwest Symposium on Image Analysis and Interpretation (SSIAI) 2018
DOI: 10.1109/ssiai.2018.8470309
|View full text |Cite
|
Sign up to set email alerts
|

Drive-Net: Convolutional Network for Driver Distraction Detection

Abstract: To help prevent motor vehicle accidents, there has been significant interest in finding an automated method to recognize signs of driver distraction, such as talking to passengers, fixing hair and makeup, eating and drinking, and using a mobile phone. In this paper, we present an automated supervised learning method called Drive-Net for driver distraction detection. Drive-Net uses a combination of a convolutional neural network (CNN) and a random decision forest for classifying images of a driver. We compare t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 9 publications
(11 reference statements)
0
28
0
Order By: Relevance
“…1). Majdi et al [26] proposed Drive-net, a method that uses a combination of a CNN and a random decision forest to classify driver images. Driver-net achieved a detection accuracy of 95% on the Kaggle dataset.…”
Section: Inceptionv3 Without a Classification Layermentioning
confidence: 99%
“…1). Majdi et al [26] proposed Drive-net, a method that uses a combination of a CNN and a random decision forest to classify driver images. Driver-net achieved a detection accuracy of 95% on the Kaggle dataset.…”
Section: Inceptionv3 Without a Classification Layermentioning
confidence: 99%
“…The results showed that the system could achieve 96.31% accuracy on the AUC Distracted Driver dataset. However, in recent works [19,20,[24][25][26], only spatial information was considered, but temporal information, related to important cues for behavior recognition, were discarded. In Reference [48], Chuang et al proposed a skeleton-based and a point-cloud approach with multiple views based on Kinect depth cameras for driver behavior recognition, and LSTM was adopted to train the behavior model.…”
Section: Related Workmentioning
confidence: 99%
“…Although distracted behavior analysis was studied in recent works [19,[24][25][26], only spatial information was considered while temporal information was discarded. In previous studies of action recognition, many network configurations were designed to integrate the spatial and temporal information, for example, 2D ConvNets + LSTM [41,42], 3D ConvNet [43,44], and two-stream network [27].…”
Section: Temporal Stream Convnetmentioning
confidence: 99%
See 2 more Smart Citations